THER-33. TOCILIZUMAB AS A POTENTIAL NOVEL THERAPY IN PATIENTS DIAGNOSED WITH ADAMANTINOMATOUS CRANIOPHARYNGIOMA. (23rd April 2019) - Grob, Sydney; Donson, Andrew; Prince, Eric; Vijmasi, Trinka; Foreman, Nicholas; Dahl, Nathan; Vibhakar, Rajeev; Mirsky, David; Hankinson, Todd; Levy, Jean Mulcahy
Abstract: Adamantinomatous craniopharyngioma (ACP) makes up between 6–8% of pediatric brain tumors and is the most common pediatric tumor arising in the sellar/suprasellar region of the brain. The 10-year survival for patients diagnosed with craniopharyngioma ranges between 64–92%, but given complicating factors such as its location, common cyst formation, and potential hypothalamic infiltration, there is significant morbidity in this population. There are a number of therapy options for children with craniopharyngioma including surgery, radiation, and cyst-directed therapies such as Interferon and Bleomycin. Research has raised concerns regarding efficacy and morbidity induced side effects with these conventional therapies and with difficulty in treating recurrent primary cystic ACP. Evidence from our group and others have shown that the cystic and solid tumor components of craniopharyngioma have high levels of IL-6R and IL-6, providing a potential target for therapy. Tocilizumab acts against soluble and membrane bound IL-6R, leading to the possibility that it may offer benefit for some patients with ACP. Two patients with recurrent primary cystic craniopharyngiomas treated at Children's Hospital Colorado were offered systemic administration of the IL-6R antagonist, tocilizumab or a combination of tocilizumab and bevacizumab on a compassionate use basis. Both patients' tumors had a significant response, with decreased cystic burden, supporting the assertion that tocilizumab and bevacizumab may be an option for patients suffering from cystic craniopharyngioma.